THE PECULARITIES OF ARGINASE THERMIC INACTIVATON (Proceedings of the YSU B: Chemical and Biological Sciences, 2001)
The effect of temperature on conformation and catalytic activity of bovine liver arginase in aqueous solutions was studied. During the experiment ([Ca]=4.2·I0–7M, pH 9.5) under the influence of the temperature of 60–80℃ the inactivation of the arginase was accompanied by a decrease of Michaelis constant values and reduction of triptophane fluroscence. In the presence of ornithine the sensitiveness of the enzyme towards the temperature effect is considerably increased. The results led to the conclusion that the thermic inactivation of arginase in a solution is a result of the violation of native conformational condition, not directly affecting the active center of the enzyme. The measuring of intensity of triptophane fluroscence can be successfully used to registrate conformational changes in arginase solutions under existing conditions.